Business sustainability through e-commerce: a myth or reality in Nigeria - Akintoye, Ishola R.; Ajayi, Modupe; Joshua, Abimbola; Okunlola, Abiodun F. (Business: Theory and Practice, 2022)
A succinct exploration of business sustainability via an e-commerce platform was examined in the study. Its myth and reality permeate its adoption, use, and acceptability within the context of our economic, social, and environmental assumptions were also validated. To achieve its aim, exploratory methodology, which compared benefits and challenges among the three main elements – business, users, and authority; in the application of the e-commerce platforms and channels in the country was examined. The result showed mixed outcomes. On one side, there are huge benefits to businesses in adopting e-commerce while on the other, challenges such as optimal patronage due to cultural trust gaps, user-confidence, poor connectivity, and government selective policy drive. Based on this outcome, it is concluded that; business sustainability via e-commerce in the country is relatively weak and can be improved upon if, end-users policy drive is taken into serious consideration.